Sexual gratifcation in Indonesia's criminal law - Azahrah, Wahida; Disemadi, Hari Sutra; Jaya, Nyoman Serikat Putra (Legality : Jurnal Ilmiah Hukum, 2020)
The Corruption Crime Act has the term â€œgratificationâ€ as part of a criminal act of corruption. Gratuities are regulated in Article 12B (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001. But now a new type of gratification is emerging, sexual gratification. The research method used in this paper is normative research, which is the statutory approach, historical approach and the conceptual approach. Overall regarding sex gratification, there is still a lack of norms, which can be classified into acts of sexual gratification.